Enhancing Electrical Substation Training through Multi-User Virtual Reality Techniques - Neto, Jair; Cyrino, Gabriel; Lamounier, Edgard; Cardoso, Alexandre; Campos, Davidson; Oliveira, Jader; Queiroz, Lilian F. (Anais do Simpósio de Realidade Virtual e Aumentada (SVR), 2023)
Virtual Reality (VR) training is a potential solution for reducing the frequency of chance risks within electrical substations. However, many tools developed for this purpose do not support the concurrent training of several users. The lack of this feature does not completely mimic a company’s reality, since most training is undertaking, in real life, with many operators together. Thus, this work presents the development of a system for the utilization of multi-user VR-based techniques in electric substation training. This application has no intention to replace the trainer, but rather to provide an auxiliary and supportive tool that can be used and improved to reduce the risk chance associated with unpreparedness and inadequate training. This involves designing and implementing a server-side architecture that can handle data storage, and communication with clients. The results demonstrate positive progress and effectiveness of the system, with specific strengths in addressing prior knowledge requirements, ease to use, and a self-sufficiency of the tool itself. By creating a consolidated training platform and addressing the areas of improvement highlighted in the results, the tool has the potential to be highly valuable for future training in electrical substation companies.